If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + -17 = -8 Reorder the terms: -17 + -12x = -8 Solving -17 + -12x = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + -12x = -8 + 17 Combine like terms: -17 + 17 = 0 0 + -12x = -8 + 17 -12x = -8 + 17 Combine like terms: -8 + 17 = 9 -12x = 9 Divide each side by '-12'. x = -0.75 Simplifying x = -0.75
| 1/3(2x-5)=3/4(x-4) | | (X^2/x+40)=20 | | -6(x+2)+3x+7=8x+11 | | -7(-s+9)+3(-5+2s)= | | 14y+4=3y-5 | | (5-3x)=7x+4 | | X^2/x+40=20 | | -138+4x+9x=83 | | 2(2x-3)=14 | | C=52+0.20x | | C=10.8w+0.41 | | 0.63=log(x) | | 7v(6-2v)=12 | | 48/10 | | (2x)-6(x/3)=x+3 | | z^3-3z^2+4=0 | | 2(3h+2)-4h= | | 4xsquared+16x=20 | | Y/2=62 | | x-5y=-28 | | 2x^2+32x-3888=0 | | -6x-24=-4x-8 | | 6a+4a+7a-3b-2a= | | 3(4p-5)=12 | | 5x=5x-20 | | m^2+9m=14 | | -4x-3(-2x-17)=33 | | 7x-41=-13 | | -8(2x-1)-6-3(x-2)= | | 2x+3-x=x+3 | | 2-4x=11/3 | | 6x+33=15-48 |